Héloïse d"Argenteuil se filosofiese uitset - Beukes, Johann (HTS teologiese studies, 2019)
The philosophical output of Héloïse d’Argenteuil. This article attempts to deconstruct the overhyped erotic relationship between the philosopher-monk Peter Abelard (1079–1142) and philosopher-nun Héloïse d’Argenteuil (ca. 1100–1164), by surveying Héloïse’s extant texts (Epistolae duorum amantium, Episto lae Heloissae and Problemata Heloissae) as such, isolating three themes in her philosophical output: her concept of Cicerian love, her criticism of marriage and her notion of moral and material responsibility, which includes her understanding of an ethics of attitude and intention. When Héloïse is read against the grain of the standardised Abelard-reception (which holds Héloïse as at best a productive correspondent of Abelard, yet a mere muse for his extensive academic output), she is brought into perspective as an independent thinker, who deserves more intellectual respect than to be caricaturised as either Abelard’s secret young lover, or his unwilling wife. When her texts are read as independent outputs, albeit often in the form of correspondence, she steps forward as the ‘first female philosopher of the Middle Ages’. Her relationship with Abelard, important as it was for both of them, is secondary to her standing as a philosopher proper.